Gendered Impressions of Issue Publics as Predictors of Climate Activism - Geiger, Nathaniel; Swim, Janet Kay (Frontiers in Communication, 2018)
The present work explores how gendered impressions of issue publics (i.e., those who are well informed about, and have strong opinions about, a given topic) can predict individuals’ interest in engaging in activism either consistent with the issue public’s position or diametrically opposed to its position. In two studies (Ns = 286, 245) using MTurk samples, we explore the predictors of pro-climate and anti-climate activism based on the impressions of the climate concerned (i.e., an issue public supporting action on climate change; Study 1) and the climate dismissive (i.e., an issue public opposing action on climate change; Study 2). We relied on two complementary theoretical perspectives to make predictions: a) gender role congruity theory, which suggests that the more perceivers ascribe gendered traits to issue publics that match the perceiver’s own gender, the more they will engage in behavior associated with that issue public , and b) social value of attributes which suggests that various components of femininity and masculinity may be universally valued (i.e., positive aspects of masculinity) or devalued (i.e., negative aspects of femininity) by society regardless of perceivers’ own gender. Predictions made by gender role congruity theory were not supported: men did not prefer engaging in activism when they perceived the relevant issue public to be more masculine and women did not tend to prefer engaging in activism when they perceived the relevant issue public to be more feminine. In contrast, results were consistent with social value of attributes predictions suggesting the importance of positive components of masculine impressions of issue publics in promoting activism consistent with the issue public and discouraging activism diametrically opposed to the issue public Yet, results also point to the potential “dark side” of appearing masculine: ascribing negative masculine traits to an issue public was associated with increased willingness to engage in activism diametrically opposed to the issue public and, when the issue public dismisses climate change, reduced interest in engaging in anti-climate activism. In contrast, ascribing negative feminine traits to an issue public did not uniquely predict interest in engaging in activism either supporting or opposed to the issue public.